2014
DOI: 10.1186/bcr3619
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor beta as a novel target of androgen receptor action in breast cancer cell lines

Abstract: IntroductionThe two isoforms of estrogen receptor (ER) alpha and beta play opposite roles in regulating proliferation and differentiation of breast cancers, with ER-alpha mediating mitogenic effects and ER-beta acting as a tumor suppressor. Emerging data have reported that androgen receptor (AR) activation inhibits ER-positive breast cancer progression mainly by antagonizing ER-alpha signaling. However, to date no studies have specifically evaluated a potential involvement of ER-beta in the inhibitory effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 58 publications
(62 reference statements)
1
62
1
2
Order By: Relevance
“…Previous results from this cohort suggested that the prognostic role of AR in breast cancer was dependent on the ERa status of the tumor (20). Similar hypotheses have been proposed for ERb (10), and an in vitro study suggested ERb to be the link between AR and ERa interactions (28). However, in the current study, unlike AR, ERb1 75 þ was prognostically beneficial irrespective of ERa expression.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous results from this cohort suggested that the prognostic role of AR in breast cancer was dependent on the ERa status of the tumor (20). Similar hypotheses have been proposed for ERb (10), and an in vitro study suggested ERb to be the link between AR and ERa interactions (28). However, in the current study, unlike AR, ERb1 75 þ was prognostically beneficial irrespective of ERa expression.…”
Section: Discussioncontrasting
confidence: 54%
“…The AR acts as a transcription factor and has been shown to bind to ER-regulated genes to inhibit ERdependent cell proliferation (6). Recently, in vitro studies have suggested that activated AR up-regulates estrogen receptor beta gene expression, which inhibits breast cancer cell growth (13). AR has also been suggested to interact with cell cycle checkpoint protein p21, which is involved in epidermal growth factor signaling (14).…”
Section: Introductionmentioning
confidence: 99%
“…ERβ exerts a growth and invasion inhibitory action on ERα-positive BC cells through ERβ inhibition of selective ERα gene expression (Rizza et al 2014). ARE is a short sequence of DNA located in the human ERβ gene promoter and thus AR binding to ARE upregulates these receptors; and (5) AR induces apoptosis through direct downregulation of cyclin D1 gene expression (Lanzino et al 2010).…”
Section: Figurementioning
confidence: 99%